Combination of structural and compositional factors for describing forest types using national forest inventory data - Rego, F.; Godinho-Ferreira, P.; Uva, J. S.; Cunha, J. (Monitoring and Indicators of Forest Biodiversity in Europe - From Ideas to Operationality, 2005)
For the first time in Portugal, simple variables describing the vertical structure and the composition of forests on the Portuguese mainland were included in the 2258 sample plots of the National Forest Inventory (DGF 2001). The vertical forest structure was assessed by percentage cover of seven height. classes and the composition of the different layers was described using plant species, or groups of plant species, easily identifiable in the field. Cluster analysis, in particular K-means statistics, was performed using combinations of vertical structure and compositional data, resulting in ten main natural groups or forest types: 1) Quercus pyrenaica forests; 2) Other deciduous oak forests; 3) Arbutus unedo forests; 4) Cistus shrubs; 5) Cytisus shrubs; 6) Acacia forests; 7) Quercus suber forests; 8) Pinus pinaster forests; 9) Eucalyptus forests; and 10) Other forests. The last four groups were further subdivided according to the vertical structure resulting in twenty final forest types. The geographical distribution of these forests types and the implications for biodiversity and other forest issues are presented and discussed.
The following values have no corresponding Zotero field: periodical: Monitoring and Indicators of Forest Biodiversity in Europe - From Ideas to Operationality issue: 51 pub-location: TORIKATU 34, FIN-80100 JOENSUU, FINLAND
Keywords: Biodiversity; composition; forest types; national forest inventory; vertical structure